2020
DOI: 10.1016/j.nicl.2020.102392
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of verbal working memory in children with epilepsy with centro-temporal spikes

Abstract: Highlights We investigated working memory in patients with ECTS and age-matched controls using a verbal working memory task. Children with ECTS showed altered behavioral and fMRI responses to verbal working with increasing difficulty level. Children with ECTS demonstrated reduced capacity to sustain high WM load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 103 publications
1
2
0
Order By: Relevance
“…It was previously reported that children with BECTS had early cognitive impairment, similar to the findings obtained [14]. Further studies also revealed that children with BECTS not only had a lower accuracy and response time in working memory tasks [39] but also performed poorly in reading comprehension and word reading [40]. Although there was no significant difference in test scores between the U-BECTS and B-BECTS groups, children in the B-BECTS group scored significantly lower in the Perceptual Reasoning Index (PRI) test than those in the control category.…”
Section: Clinical Characteristics and Neuropsychological Testssupporting
confidence: 85%
See 1 more Smart Citation
“…It was previously reported that children with BECTS had early cognitive impairment, similar to the findings obtained [14]. Further studies also revealed that children with BECTS not only had a lower accuracy and response time in working memory tasks [39] but also performed poorly in reading comprehension and word reading [40]. Although there was no significant difference in test scores between the U-BECTS and B-BECTS groups, children in the B-BECTS group scored significantly lower in the Perceptual Reasoning Index (PRI) test than those in the control category.…”
Section: Clinical Characteristics and Neuropsychological Testssupporting
confidence: 85%
“…A previous magnetoencephalographic study reported that better cognitive performance was related to higher C and lower L values in certain frequency bands, which make the brain integrate and process information more effectively [61,62]. Moreover, differing from their healthy counterparts in how they controlled working memory processes, children with BECTS showed reduced activation in the frontal, temporal, and parietal regions as well as in behavioral performances [39]. To assess the impact of dominant hemisphere on cognitive profiles, we investigated separately the correlation between clinical characteristics, cognitive function, and FC network parameters in patients with U-BECTS with left or right spikes.…”
Section: Correlation Analysismentioning
confidence: 94%
“…There was also a significant positive correlation between abnormal EC and the number of seizures in the medicated group, which indicated that abnormal EC could be improved by effective antiseizure medications (ASMs) and reductions in the number of seizures. A previous study of fMRI and verbal working memory tasks in BECTS patients also found that the greater the number of seizures, the greater the abnormal activation of these regions [ 37 ]. It was also found that the association between altered EC strength and cognitive impairment (of verbal memory and language function) was affected by both seizure frequency and lateralization in patients with temporal lobe epilepsy (TLE) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%